Industrial automation and robotics - Gupta, A. K. (College teacher of mechanical engineering); Arora, S. K. (College teacher); Westcott, Jean Riescher (Mercury Learning and Information, 2017)
Presenting an introduction to the multidisciplinary field of automation and robotics for industrial applications, this book initially covers the important concepts of hydraulics and pneumatics and how they are used for automation in an industrial setting before moving to a discussion of circuits and using them in hydraulic, pneumatic, and fluidic design. -- Edited summary from book.
Includes index.
Keywords: Robots, Industrial.; Automation.; elektronické knihy; electronic books